Sigmoid Colon Cancer Masquerading as a Right Incarcerated Inguinal Hernia: A Case Study and Literature Review - Zhang, Jianfeng; Tang, Yujie; Wu, Xueliang; Wang, Guiying; Li, Tian (Frontiers in Surgery, 2022)
Background Indirect inguinal hernia and sigmoid colon cancer are both common diseases, but carcinoma within the hernia sac is rare. We present a case of sigmoid colon cancer masquerading as a right incarcerated inguinal hernia. Since such a presentation is rare, and the correct diagnosis is usually made intraoperatively, there is still no consensus on the best treatment modality for such patients. Case Presentation A 70-year-old man presented to our hospital on September 20, 2020, with a right inguinal mass that had been painful for half a month, accompanied by symptoms of difficult defecation. The bulge was originally found at least 60 years before admission. There was no pain at the time; however, the mass enlarged progressively during the last 3 years. The right scrotum and groin area were obviously enlarged (approximately 20 cm × 20 cm) and tender. Inside the scrotum, a circumscribed medium-hard mass (diameter 5 cm) that was palpable, with ill-defined borders and translational mobility was detected. The computed tomography (CT) scan showed a right blood vessel-containing strangulated inguinal hernia; the sigmoid colon showed focal wall thickening as it was in proximity to the inguinal hernia. Based on the biopsy results, a pathologic diagnosis of high-grade intraepithelial neoplasia was made. The preliminary diagnosis was that of sigmoid carcinoma and right incarcerated inguinal hernia. Emergency laparoscopic exploration, open sigmoid radical resection andright inguinal hernia repair were performed under general anesthesia. The patient recovered successfully and was discharged one week after the operation. One month after surgery, no discomfort and signs of recurrence were found. Conclusions The combination of colorectal cancer and inguinal hernia is uncommon, and detailed preoperative physical examination and imaging studies may contribute to the establishment of a correct diagnosis. The selection of appropriate surgical methods ensures good therapeutic results.